Linking plant litter microbial diversity to microhabitat conditions, environmental gradients and litter mass loss: Insights from a European study using standard litter bags. (May 2020) - Pioli, Silvia; Sarneel, Judith; Thomas, Haydn J.D.; Domene, Xavier; Andrés, Pilar; Hefting, Mariet; Reitz, Thomas; Laudon, Hjalmar; Sandén, Taru; Piscová, Veronika; Aurela, Mika; Brusetti, Lorenzo
Abstract: Plant litter decomposition is a key process for carbon dynamics and nutrient cycling in terrestrial ecosystems. The interaction between litter properties, climatic conditions and soil attributes, influences the activity of microorganisms responsible for litter mineralization. So far, studies using standardized litters to investigate the response of bacterial and fungal communities under different environmental conditions are scarce, especially along wide geographic ranges. We used a standardized protocol to investigate the diversity of bacteria and fungi in plant litter with the aim of: (i) comparing the microbial communities of native and exotic litters with the community of local soil along a European transect from northern Finland to southern Italy, (ii) defining whether and to what extent, litter types with different traits represent selective substrates for microbial communities, (iii) disentangling the abiotic drivers of microbial diversity, and (iv) correlating the microbial diversity and species co-occurrences patterns with litter mass loss. We buried native litter and three exotic standardized litters ( Deschampsia cespitosa, rooibos tea and green tea) at 12 European study sites. We determined litter mass loss after 94 days. We used an automated molecular DNA-based fingerprinting (ARISA) to profile the bacterial and fungal communities of each litter type and soil (180 samples in total). Microbial communities in native and exotic litters differed from local soil assemblages. Green tea and D. cespitosa litter represented more selective substrates compared to native litter and rooibos. Soil moisture and soil temperature were the major drivers of microbial community structure at larger scales, though with varying patterns according to litter type. Soil attributes (i.e. moisture and C/N ratios) better explained the differences in microbial abundances than litter type. Green tea degraded faster than all other litter types and accounted for the largest number of positive co-occurrences among microbial taxa. Litter mass loss was positively correlated with fungal evenness and with the percentage of positive co-occurrences between fungi. Our findings suggest that the microbial community at larger scales reflects the complex interplay between litter type and soil attributes, with the latter exerting a major influence. Mass loss patterns are in part determined by inter- and intra-kingdom interactions and fungal diversity. Highlights: Litter types with different traits act as ecological filters for bacteria and fungi. Edaphic conditions exert a major influence on microbial diversity. Litter decomposition is related to fungal diversity and microbial co-occurrences. Using standard litter types allow comparisons across wide geographic ranges.